Ben Hutchinson. Comparative Literature: A Very Short Introduction. Oxford UP, 2018. - Toloo Riazi (Studies in 20th & 21st Century Literature, 2019)
Review of Ben Hutchinson. Comparative Literature: A Very Short Introduction. Oxford UP, 2018.
Keywords: Comparative literature; history; future